Oligochitosan fortifies antioxidative and photosynthetic metabolism and enhances secondary metabolite accumulation in arsenic-stressed peppermint - Ahmad, Bilal; Dar, Tariq Ahmad; Khan, M. Masroor A.; Ahmad, Ajaz; Rinklebe, Jörg; Chen, Yinglong; Ahmad, Parvaiz (Frontiers in Plant Science, 2022)
The present study was designed to investigate whether application of irradiated chitosan (ICn), a recently established plant growth promoter, can prove effective in alleviating arsenic (As) stress in peppermint, a medicinally important plant. This study investigated how foliar applications of ICn alleviated As toxicity in peppermint (Mentha piperita L.). Plants were treated with ICn (80 mg L−1) alone or in combination with As (10, 20 or 40 mg kg−1 of soil, as Na2HAsO4·7H2O) 40 days after transplanting (DAT) and effects on the growth, photosynthesis and antioxidants were assessed at 150 DAT. As stress, severely decreased plant growth, photosynthesis, and altered enzymatic (ascorbate peroxidase, superoxide dismutase) and non-enzymatic (glutathione) antioxidants. As applied at 40 mg kg−1 significantly decreased the content of essential oil (EO) and total phenols in peppermint by 13.8% and 16.0%, respectively and decreased phenylalanine ammonia lyase (PAL) and deoxy-D-xylulose-5-phosphate reducto-isomerase (DXR) activities by 12.8% and 14.6%, respectively. Application of ICn mitigated the disadvantageous effects caused due to As toxicity in peppermint by improved activities of antioxidative enzymes, photosynthesis and increased accretion of secondary metabolism products (EOs and phenols). An enhancement of total phenol (increased by 17.3%) and EO (36.4%) is endorsed to ICn-stimulated enhancement in the activities of PAL and DXR (65.9% and 28.9%, respectively) in comparison to the control. To conclude, this study demonstrated that foliar application of ICn (80 mgL−1) effectively promoted the growth and physiology of peppermint and eliminated As-induced toxicity to achieve high production of EO-containing crops grown in metal-contaminated soils.